ANALISIS PELAKSANAAN POSYANDU LANJUT USIA DI PUSKESMAS BANDARHARJO DAN KROBOKAN KOTA SEMARANG - Ade Kurniasari; Antono Suryoputro; Septo Pawelas Arso; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2018)
Elderly is someone aged 60 years and over. The increasing number of elderly has received the attention of the government by making the elderly health as a priority by the issuance of PMK No. 67 of 2015. The report of the elderly health service coverage in Semarang City 2017 showed that there were 8 puskesmas that didn’t reach the target (67%). Puskesmas Bandarharjo has the lowest coverage and Krobokan has the highest coverage. To increase this coverage, puskesmas developed posyandu for elderly. A preliminary study at Puskesmas Bandarharjo showed that the coverage of pre-elderly and elderly services  was below the target, the elderly who were served in the posyandu were only 41,87%, the coverage of elderly who measured blood pressure at posyandu was fluctuated, peaking at 30.5% of the total elderly who were served. This study aims to analyze the implementation of elderly posyandu in Puskesmas Bandarharjo and Krobokan working area with a system theory approach. This study uses a qualitative research method with in-depth interview. Cadres are the main informants, while stakeholder of elderly programs at puskesmas, stakeholder of elderly program at  Semarang Health Department and the elderly are the triangulation informants. The result of this study shows that there were similarities in the problems between the two puskesmas including inadequate human resources, the lack of trainings for cadres, puskesmas staffs’ tardiness or absence, insufficient funds, incomplete facilities, the fact that the target of some posyandu is only elderly and doesn’t include the pre-elderly people, the lack of clarity in terms of organizational structure, posyandu did not monitor the elderly to check their Hb and blood glucose, and the lack of community support. Other problems found in puskesmas Bandarharjo include posyandu which had not been functioning for one year, the implementation of posyandu that had not been in accordance with guidelines, and the fact that not all of the cadres were able to write the report.